TYPE AND FREQUENCY OF CANINE AGGRESSIVENESS TO HUMANS IN PATIENTS OF A VETERINARY CLINIC IN LIMA - Sal y Rosas M., Eduardo (2010)
The purpose of this study was to determine the type and frequency of aggressiveness directed to the human, and to identify the situations in which they occur. A survey was conducted on 405 owners of patients of the Small Animal Clinic of the Faculty of Veterinary Medicine, San Marcos University. All animals were without apparent neurological alterations. Results indicated that 27.2% of dogs showed some sort of aggressiveness, mainly light and medium intensity; where the dominant type was the most frequent (50.0%). The dominant, territorial and predatory aggressiveness was statistically associated with sex of the animal (p<0.05), as well as the intensity of the dominant aggressiveness (p<0.05), where males were more aggressive. The most frequent situation where dominant aggressiveness was manifested occurred when getting closer or trying to touch the dog while was eating or holding an object the dog considered its property (90.9%).